Design and Application of Intelligent Building Environment Monitoring System Based on Wireless Sensor Network - Du, Liang (Informatica, 2024)
Based on the low-power adaptive clustering routing algorithm, an improved method is proposed to solve the high energy consumption and uneven distribution of cluster heads. According to the results, the monitoring area was 300×300m, the cluster heads of the improved algorithm were relatively evenly distributed in various regions. When the time was 261 rounds, the surviving nodes in the improved algorithm decreased. As time increased, the surviving nodes in the improved algorithm increased. The energy use speed of the improved algorithm is the slowest. Because it changed the conditions for the low-power adaptive clustering routing algorithm to re-select cluster heads and clustering methods, it reduced the energy consumption during cluster formation. Improved algorithms could better reduce energy use and extend network lifespan. The actual and predicted values of the building environment detected by the improved system almost overlapped, indicating that the temperature monitoring accuracy of the system was high, reaching 98.6%. The robustness is significantly enhanced. This system can monitor the internal environment of buildings in real time, achieve optimized energy allocation and rational utilization, monitor equipment energy consumption, ensure the reliability of electrical equipment operation, and improve the energy utilization rate. This provides a new reference direction for environmental monitoring work.